Strategi Pembelajaran Program Bahasa Arab dan Bahasa Inggris Untuk Meningkatkan Daya Saing Alumni Di Era Revolusi Industri 4.0 Di Pondok Pesantren Mamba’us Sholihin Suci Manyar Gresik - Husna, Ema Umiatul; Nisa', Khoirun (Universitas KH. A. Wahab Hasbullah, 2021)
This study aims to obtain empirical evidence regarding the Arabic and English Language Program Learning Strategies to Increase Alumni Competitiveness in the Era of the Industrial Revolution 4.0. This research is expected to be used as material for consideration by foreign language education institutions in determining language learning strategies, and the results of this study can add to the literature and can be used as reference material for further research. The research method used is descriptive qualitative analysis. Data collection used was interviews, observation and documentation. Data collection in the field will be carried out in 2020. The results showed that the Arabic and English learning strategies at the Manyar Gresik Islamic boarding school were effective and efficient. Where the concept of implementation in the Arabic and English language program's learning strategy has advantages that are able to form alumni to face challenges and be able to compete in this era of revolution 4.0. but in a lesson there are also inhibiting factors that will be obstacles that have an impact on the language skills that have been learned at the Manyar Gresik Mamba'us Sholihin Suci Islamic sboarding school.